Election, Favoritism, and Freedom: Towards a Modern Jewish Theology of Matrilineal Descent - Isseroff, Judah (Modern theology, 2023)
This article offers an account of the broad theological contours of the Jewish practice of matrilineal descent. I make the case that matrilineality epitomizes God's contingent preference in favoring and electing Israel. I link Mara Benjamin's recent work to recuperate asymmetrical power relations for feminist theology to the asymmetrical relationship inherent in God's election of Israel. With Benjamin, I emphasize the importance of contingency, vulnerability, and favoritism for divine and parental love. I then read the opening parable in the tractate of Avodah Zarah for one Talmudic strategy for reckoning with the contingency of election. In Avodah Zarah, election's contingency is qualified by the concept of zekhut avot—the merit of the patriarchs. From here, I turn to the work of Jon Levenson for an account of the construction of zekhut avot in the Genesis stories. I show that the merit of the patriarchs is defined by the patriarchal encounter with the trial of favoritism. For the Israelites after Genesis, a decisive consequence of zekhut avot is that all of Jacob's (Israel's) descendants become beloved of God. The contingent transmission of the covenant thus transforms from inscrutable divine choice to the still-contingent power of ancestry. The article closes with an interpretation of the rabbinic concept of zekhut imahot—the merit of the matriarchs. The preferred or preferring matriarch is decisive for determining the next beloved son in Genesis. The article argues that matriarchal merit is not tied to any essential construction of gender, but to the capacity to exercise freedom under conditions of providential silence. I contend that the practice of matrilineal descent re-inscribes matriarchal merit for every generation of the Jewish people.